Reception. (April 2020) - Bridges, Emma; Stead, Henry
Abstract : Chris Davies' Blockbusters and the Ancient World is the latest addition to a growing body of scholarly literature on cinematic receptions of antiquity. The author takes as his focus the swathe of ancient world epics produced since the 9/11 terrorist attacks in 2001, ranging from movies set in the ancient Greek world (including the 2004 films Troy and Alexander, and, from 2007, 300 ) to the Roman occupation of Britain – as seen in King Arthur (2004), The Last Legion (2007), Centurion (2010), and The Eagle (2011) – as well as those which concentrate on aspects of Christianity ( Agora, of 2009, set in Alexandria in the early fifth century ce, as contrasted with the 2004 biblical epic The Passion of the Christ ). Structured around a series of case studies of these individual films, the book undoubtedly adds a set of valuable contributions to the scholarly literature on each piece; its real strength lies, however, in the way in which the author draws comparisons between these case studies while simultaneously situating the movies within their wider historical, political, and cultural contexts. Davies' introduction alone – with a broad overview of the development of cinematic depictions of antiquity from the birth of cinema to contemporary productions, along with definitions of key terms – provides an excellent starting point for those new to thinking about ancient world films, and a comprehensive filmography of works referenced is a useful research tool. There is much here too, however, which will be of value to those seeking more in-depth discussion. Detailed analysis of the films themselves – with attention to staging, casting, and characterization – is accompanied by discussion of critical responses and evidence from published interviews with directors and producers. The author is careful to point out that artistic products often resist straightforward interpretation, and that multiple readings of each film are possible (for example, the critical reception of a movie may infer a different relationship to contemporary politics than the stated intentions of its creative team). He also explores the development and fluidity of genres, and the ways in which several of these films hybridize more than one genre (for example, traces of the western are strongly evident in the Roman Britain epics; and The Passion of the Christ carries striking elements of the horror genre). What results is a sensitive exploration of the films' relationship to US politics, in the particular context of the 'War on Terror' and the US-led invasions of Iraq and Afghanistan, which examines ways in which the films 'have inspired allegorical and metaphorical readings in which the past has been used to contextualise, warn or parallel the present' (209).